Pembangunan Desa Melalui Pemberdayaan Masyarakat Bidang Ekonomi Pada Desa Pemecutan Kaja, Kecamatan Denpasar Utara, Kota Denpasar - Pratama, Marcellino; Yudartha, I Putu Dharmanu; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2019)
ABSTRACT Village development in PemecutanKaja Village was increased through community and government participation. This was done tozovercomeztheproblemzof poverty in PemecutanKaja Village. The poverty rate in PemecutanKaja Village is the highest in Denpasar, even though it has the largest APBDes. This research is intended to describe the role of community empowerment as an effort to realize development in PemecutanKaja Village. Thiszresearchzwaszconductedzusing qualitative research methods through descriptive approaches such as in-depth interviews. The analysis carried out is based on the theory of development and uses the concept of economic empowerment with indicators in the form of human resources, human resources, capital and infrastructure of production and marketing. Thezresultzofthiszstudy indicate that the village development that has occurred so far is still being carried out unevenly and underdeveloped planning. Keywords:Village development, Economic empowerment